L’Incipit de Jane Eyre : l’annonce d’une quête - Elise Ouvrard (Revue LISA)
Jane Eyre, a fictitious autobiography published by Charlotte Brontë in 1847, starts with the description of a little girl enthralled by the reading of The History of British Birds. However the child is disturbed by John Reed’s noisy entrance and this interruption can be considered as the limit of the incipit according to the definition that Andrea Del Lungo gives of the term in L’Incipit Romanesque. In this first unit of text, what is quite striking is that the ekphrasis enables the narrator to give a thematic, poetic and aesthetic orientation to the novel that is being written. Indeed by describing the pictures of the book by Thomas Bewick, Jane Eyre not only gives an idea of her miserable existence but also heralds the quest she is about to undertake.